Synthesis of 2, 3-Dihydro-1,4-naphthaquinone Derivatives for Targeting the Altered Cancer Cells Metabolism (JOURNAL OF ADVANCES IN CHEMISTRY, 2008)
A new four derivatives of 2,3-Dihydro-1,4-naphthaquinonewere synthesizedas possible bioreductiveprodrugs for5-fluorouracil (5-Fu),Mercaptopurine (6-MP), N-acetyl cysteine (NAC)and 3-bromopyrovic acid (3-BPA) to selectively deliver the drugs into the cancer cells and these are:2-((5-fluoro-1,2-dihydropyrimidin-4-yloxy)methyl)-3-hydroxy naphthalene-1,4dione(compound A),2-((9H-purin-6-ylthio)-3-hydroxyl naphthalene-1,4dione(compound B)acetmido-3-((3-methyl-1,4-dihydronaphthalen-2-yl)methylthio)propanoicacid (compound C)and hydroxy-1,4-dioxo-1,4-dihydronaphthalen-2-yl)methyl3-bromo-2-oxopropanoate ( compound D)Their chemical structures were characterized by H1 NMR, IR spectroscopy and elemental microanalysis.The in vitro antitumor activity tests againstHep-2 human larynx    cancer cell lineindicated that compound A,B,C and D havesignificant  anticancer activities when compared with 5-Fu.